(3GdeNGQL aj GdMjd(B((3YfO CHj MfjaI(B)s - (3jYbhH Hf EHQGgje Hf MHjH GdCfUGQj Gdchaj GdbGVj, CHh jhSa,J (B182 (3g` s; (3QhGjI CHh jhSa jYbhHs
(3BNQgG (B:s
(3Chd HGH GdTaYg s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3QhGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B193 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B240s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B9 - (3U (B273 s
Keywords: (3Gdabg GdMfajs